2022
DOI: 10.1021/acsanm.2c03958
|View full text |Cite
|
Sign up to set email alerts
|

Pb2BiS2I3 Nanowires for Use in Photodetectors

Abstract: The multicomponent chalcogenide halides of group V and IV elements have aroused great research interest in photoelectric applications owing to their efficiency, stability, and interesting semiconducting properties. Herein, we used a hot-injection solution approach to synthesize Pb2BiS2I3 nanowires (NWs). The Pb2BiS2I3 NWs show a narrow size distribution, excellent air and thermal stabilities, and strong absorption in the visible-light region. The Pb2BiS2I3 NWs-based photodetectors exhibit excellent photorespon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This resulted in increased electrical conductivity and is the foundation of the photodetection function. Alongside the previously reported photodetection capabilities of perovskites and metal oxide semiconductors, 68 70 the test performed in this work showed that the MTO devices were able to work effectively between the green and violet light (photon energies of 2.2–3.1 eV) thanks to their moderate band gaps. This opens doors to a future violet photodetector made from the MTO nanostructures.…”
Section: Resultssupporting
confidence: 60%
“…This resulted in increased electrical conductivity and is the foundation of the photodetection function. Alongside the previously reported photodetection capabilities of perovskites and metal oxide semiconductors, 68 70 the test performed in this work showed that the MTO devices were able to work effectively between the green and violet light (photon energies of 2.2–3.1 eV) thanks to their moderate band gaps. This opens doors to a future violet photodetector made from the MTO nanostructures.…”
Section: Resultssupporting
confidence: 60%
“…Many additional compositional variations are possible within this family of mixed-metal chalcohalides, including those that contain different chalcogens (Se and Te), halogens (Cl and Br), and chalcogen-to-halogen ratios. Because there is a heightened demand to develop semiconductors that are lead-free, tin-based analogues such as Sn 2 BiS 2 I 3 and Sn 2 SbS 2 I 3 will be particularly attractive alternatives, but their solution-phase synthesis is yet to be thoroughly explored. , The methods developed in this study are a stepping stone toward synthesizing such quaternary materials. Further preparative and computational investigations of these materials will be needed to move them closer to real-life application and deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Chalcohalides are a special class of inorganic materials that have emerged as promising semiconductors for energy conversion devices . While chalcogenide semiconductors display high absorption coefficients and tunable band gaps but limited efficiency in solar devices, halide perovskites display higher power conversion efficiencies (PCEs) but lower chemical and thermal stability due to their weak ionic interactions. Occupying a promising middle between these two scenarios, mixed-ion chalcohalides are expected to combine the PCE of halide perovskites with the enhanced stability of chalcogenides. , Indeed, previous experimental and computational investigations have demonstrated the semiconducting nature of IV 2 VS 2 I 3 (IV = Sn or Pb; V = Sb or Bi) materials, with direct band gaps in the range of ∼1.2 to 2.0 eV. Because these values are near the band gap that is ideal for photovoltaics, the first solar devices with Pb 2 SbS 2 I 3 and Sn 2 SbS 2 I 3 were fabricated, revealing promising PCEs of ∼3 to 4%. The wider band gap compositions such as Pb 2 SbS 2 I 3 may also be of use in photocatalysis …”
Section: Introductionmentioning
confidence: 99%
“…The first device was fabricated by Nie et al and obtained a PCE of 4.04% using a single-step, solution-based chemical deposition process. Although this material family has been known since the 1980s, it has seen renewed interest in recent years, primarily due to its potential for optoelectronic applications. ,, …”
Section: Introductionmentioning
confidence: 99%